INCIDENCE AND TIME-TRENDS OF PREGNANCY-RELATED STROKE, THE NATIONWIDE CONCEPTION STUDY. (June 2022) - Olié, Valérie; Martin, Alice; Lailler, Gregory; Béjot, Yannick; Gabet, Amélie; Grave, Clémence; Regnault, Nolwenn; Deneux-Tharaux, Catherine; Claire, Mounier-Vehier; Tstatsaris, Vassilis; Kretz, Sandrine; Plu-Bureau, Geneviève; et al.
Abstract : Objective: Despite the potentially devastating effects of pregnancy-related stroke, few studies have been done on the incidence by type of stroke. We aimed to study the nationwide incidence rates and recent temporal trends for all types of pregnancy-related stroke and to compare this incidence with that of stroke in nonpregnant women. Design and method: We conducted a study of 6 297 698 women aged 15 to 49 years who gave birth in France between 2010 and 2018 with no history of stroke before pregnancy by collecting data from the French National Health Insurance Information System database. Poisson regression were used to estimate incidence by types of stroke for the different pregnancy periods and the incidence rate ratio of stroke in pregnant versus nonpregnant French women. Results: Among the 6 297 698 women, 1261 (24.0 per 100, 000 person-years) experienced a first ever stroke during pregnancy, peripartum, or the first 6 weeks of postpartum. Of the pregnancy-related strokes, 42.9% were ischemic (IS), 41.9% were hemorrhagic (with similar proportion of intracerebral and subarachnoid hemorrhage) and 17.4% were cerebral venous thrombosis (CVT). Compared with nonpregnant women, incidence rates of stroke were similar during pregnancy for IS (aIRR = 0.9(0.8–1.1), slightly higher for all hemorrhagic strokes (IRR = 1.4(1.2–1.8), and considerably increased for CVT (IRR = 8.1(6.5–10.1). Pregnancy-related stroke incidence rose between 2010 and 2018 for ischemic and hemorrhagic stroke but was stable for CVT. In a multivariate model, hypertensive disorders of pregnancy and chronic hypertension before pregnancy were associated with pregnancy-related stroke (OR = 4.65 (4.08–5.30); OR = 2.41 (1.89–3.06)). The risk associated with hypertensive disorders was double for hemorrhagic stroke (OR = 8.60 (7.18–10.30)). Conclusions: The risk of pregnancy related CVT was more than eight-fold higher than that observed in nonpregnant women.The incidence of pregnancy-related ischemic and hemorrhagic stroke is increasing over time, and efforts should be made in terms of prevention considering treatable cardiovascular risk factors and hypertensive disorders in pregnant women.